A concise synthesis of (4R, 5R)-(−)-muricatacin and (4R, 5R)-l-(−)-factor from d-glucono-δ-lactone. Issue 2 (15th February 2016) - Chaudhari, Dipali A.; Ingle, Arun B.; Fernandes, Rodney A.
Graphical abstract: Abstract: A concise seven-step synthesis of (4 R, 5 R )-(−)-muricatacin and (4 R, 5 R )-l -(−)-factor from inexpensive, commercially availabled -glucono-δ-lactone has been accomplished. The keys steps involve a one-pot conversion of the latter to γ-vinyl-γ-lactone, cross-metathesis and Wittig olefination. This strategy has potential for the synthesis of analogs by changing the alkyl side chain by Wittig olefination. Abstract : (4 R, 5 R )-4-Hydroxy-5-vinyldihydrofuran-2(3 H )-one: C6 H8 O3 [ α ]D 25 = +45.3 ( c 0.8, CHCl3 ) Initial source of chirality:d -glucono-δ-lactone Absolute configuration: (4 R, 5 R ) Abstract : (3 R, 4 R )-3, 4-(Isopropylidenedioxy)-hex-5-en-1-ol: C9 H16 O3 [ α ]D 25 = +14.2 ( c 1.0, CHCl3 ) Initial source of chirality:d -glucono-δ-lactone Absolute configuration: (3 R, 4 R ) Abstract : (4 R, 5 R, 2 E )-Ethyl-7-hydroxy-4, 5-(isopropylidenedioxy)hept-2-enoate: C12 H20 O5 [ α ]D 25 = +26.1 ( c 0.6, CHCl3 ) Initial source of chirality:d -glucono-δ-lactone Absolute configuration: (4 R, 5 R, 2 E ) Abstract : (4 R, 5 R, 2 E, 7 Z )-Ethyl-4, 5-(isopropylidenedioxy)heptadec-2, 7-dienoate: C22 H38 O4 [ α ]D 25 = +27.4 ( c 1.2, CHCl3 ) Initial source of chirality:d -glucono-δ-lactone Absolute configuration: (4 R, 5 R, 2 E, 7 Z ) Abstract : (4 R, 5 R )-(−)-Muricatacin: C17 H32 O3 [ α ]D 25 = −17.5 ( c 1.0, CHCl3 ) Initial source of chirality:d -glucono-δ-lactone Absolute configuration: (4 R, 5 R ) Abstract : (4 R, 5 R, 2 E, 7 Z )-Ethyl-4, 5-(isopropylidenedioxy)dec-2, 7-dienoate: C15 H24 O4 [ α ]D 25 = +10.7 ( c 0.72, CHCl3 ) Initial source of chirality:d -glucono-δ-lactone Absolute configuration: (4 R, 5 R, 2E, 7 Z ) Abstract : (4 R, 5 R )-l -(−)-Factor: C10 H18 O3 [ α ]D 25 = −27.1 ( c 0.6, CHCl3 ) Initial source of chirality:d -glucono-δ-lactone Absolute configuration: (4 R, 5 R )